2011
DOI: 10.1089/neu.2010.1624
|View full text |Cite
|
Sign up to set email alerts
|

Simvastatin Administration Ameliorates Neurobehavioral Consequences of Subarachnoid Hemorrhage in the Rat

Abstract: In the present study we assessed the neuroprotective effects of simvastatin in a rodent model of experimental subarachnoid hemorrhage (SAH). Based on recent data showing the role of statins not only in lowering the level of cholesterol but also in preventing cardiac and cerebrovascular damage in risk population, and in decreasing vasospasm and delayed ischemia after aneurysmal SAH, we investigated the neuroprotective effects of intraperitoneal administration of simvastatin (40 mg/kg/day for 5 consecutive days)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 58 publications
0
7
0
Order By: Relevance
“…[67][68][69] Beam traversing times were shown to be higher on days 1 to 4 after SAH induction in rats. [67][68][69] There were no significant differences in the beam walking test in an endovascular perforation model of SAH 3, 7, 14, and 21 days after SAH in rats; however, the parameter used (% impaired steps) was different from that used in the previous studies. 70 The beam balance test offers flexibility in measurements that can make experiments conducted in different laboratories difficult to compare.…”
Section: Beam Balance and Beam Walking Testmentioning
confidence: 94%
“…[67][68][69] Beam traversing times were shown to be higher on days 1 to 4 after SAH induction in rats. [67][68][69] There were no significant differences in the beam walking test in an endovascular perforation model of SAH 3, 7, 14, and 21 days after SAH in rats; however, the parameter used (% impaired steps) was different from that used in the previous studies. 70 The beam balance test offers flexibility in measurements that can make experiments conducted in different laboratories difficult to compare.…”
Section: Beam Balance and Beam Walking Testmentioning
confidence: 94%
“…Animal studies have demonstrated that statins may ameliorate early brain injury after experimental SAH 102 and improve neurocognitive outcomes. 103 To date, four prospective, randomized, placebo-controlled trials have been published evaluating the efficacy of statins in the prevention of DCI. These investigated a combined total of 190 patients with three of the studies trialling simvastatin 80 mg for 14-21 days 104 -106 and one study trialling pravastatin 40 mg for a maximum of 14 days.…”
Section: Statinsmentioning
confidence: 99%
“…Atorvastatin can reduce the incidence and severity of CVS and suppress a biomarker of cerebral ischemia after aSAH (20). Simvastatin has a beneficial therapeutic effect on reducing cognitive dysfunction after aSAH (16). Clinical trials have demonstrated that simvastatin reduces CVS and mortality and improves functional outcomes, although these findings were not statistically significant (4).…”
Section: Introductionmentioning
confidence: 99%